Is there Needed an Industry Approach on Corporate Default Risk? Case Study on Companies Listed on Romanian Stock Exchange - Cristina Maria Triandafil; Petre Brezeanu; Marius Petrescu; Leonardo Badea (Theoretical and Applied Economics, 2009)
This paper focuses on applying Black and Scholes structural approach on credit risk in the case of the companies listed on Romanian Stock Exchange. We conduct a case-study on 35 companies belonging to five industries (energetic, materials, chemistry, pharmaceuticals, equipments) during a period of 10 years in order to highlight out default point/threshold and its essential factors evolution across industries. Research approach is concentrated also on the specific characteristics of the Romanian capital market (especially in terms of illiquidity and lack of transparency additional costs), macroeconomic environment and corporate finance decision process. We compute default point from the perspective of the arbitrage between assets and leverage; in accordance with the most recent theories on specific features corporate default within emerging countries (Galytskyy, 2006), a key element will be represented by the assets volatility which will be correlated with the country risk premium in order to highlight out a potential macroeconomic impact on corporate failure.